Analisis Pengaruh Realisasi Penanaman Modal Dalam Negeri pada Sektor Perkebunan, Sektor Industri Makanan Terhadap Kemiskinan di Sumatera Utara - Syah Putera Adrianto; Rahmad Sembiring; Annisa Ilmi Faried (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to examine the effect of Domestic Investment (PMDN) in the plantation and food industry sectors on the poverty rate in North Sumatra Province during the period 2010–2023. The time series data were obtained from the Central Statistics Agency (BPS) and the Investment Office of North Sumatra Province. The research method used is multiple linear regression with the assistance of SPSS software. The results indicate that PMDN in the plantation sector has a significant effect on reducing the poverty rate, while PMDN in the food industry sector does not show a significant partial effect. However, simultaneously, both sectors significantly influence poverty levels. These findings suggest that investment policies should focus on the plantation sector in order to expand employment opportunities and improve the standard of living of the community.